Generation and detection of pure valley current by electrically induced Berry curvature in bilayer graphene - Shimazaki, Y.; Yamamoto, M.; Borzenets, I. V.; Watanabe, K.; Taniguchi, T.; Tarucha, S. (Nature physics, 2015)
Bilayer graphene can host topological currents that are robust against defects and are associated with the electron valleys. It is now shown that electric fields can tune this topological valley transport over long distances at room temperature. The field of ‘Valleytronics’ has recently been attracting growing interest as a promising concept for the next generation electronics, because non-dissipative pure valley currents with no accompanying net charge flow can be manipulated for computational use, akin to pure spin currents 1 . Valley is a quantum number defined in an electronic system whose energy bands contain energetically degenerate but non-equivalent local minima (conduction band) or maxima (valence band) due to a certain crystal structure. Specifically, spatial inversion symmetry broken two-dimensional honeycomb lattice systems exhibiting Berry curvature is a subset of possible systems that enable optical 2 , 3 , 4 , 5 , magnetic 6 , 7 , 8 , 9 and electrical control of the valley degree of freedom 10 , 11 , 12 . Here we use dual-gated bilayer graphene to electrically induce and control broken inversion symmetry (or Berry curvature) as well as the carrier density for generating and detecting the pure valley current. In the insulating regime, at zero-magnetic field, we observe a large nonlocal resistance that scales cubically with the local resistivity, which is evidence of pure valley current.